The Identification of Plasma Exosomal miR-423-3p as a Potential Predictive Biomarker for Prostate Cancer Castration-Resistance Development by Plasma Exosomal miRNA Sequencing - Guo, Tianyu; Wang, Yang; Jia, Jing; Mao, Xueying; Stankiewicz, Elzbieta; Scandura, Glenda; Burke, Edwina; Xu, Lei; Marzec, Jacek; Davies, Caitlin R.; Lu, Jiaying Jasmin; Rajan, Prabhakar; et al. (Frontiers in Cell and Developmental Biology, 2021)
Castration-resistance is the main issue in the treatment of prostate cancer. Biomarkers, in particular those can be detected by non-invasive liquid biopsy approach, to improve early detection/prediction of castration-resistance prostate cancer (CRPC) occurrence are critical for therapeutic outcome. Therefore, we investigated the plasma exosomal miRNAs associated with prostate cancer castration-resistance and their potential to be developed into non-invasive early detection biomarkers for CRPC. RNA-sequencing, which generated approximately five million reads per patient, was performed to identify differentially expressed plasma exosomal miRNAs between 24 treatment-naive prostate cancer and 24 CRPC patients. RT-qPCR was used to confirmed the differential expressions of six exosomal miRNAs, miR-423-3p, miR-320a, miR-99a-5p, miR-320d, miR-320b, and miR-150-5p (p= 7.3×10-8, 0.0020, 0.018, 0.0028, 0.0013, and 0.0058, respectively) firstly in a validation cohort of 108 treatment-naive prostate cancer and 42 CRPC patients. The most significant differentially expressed miRNA, miR-423-3p, associated with CRPC with area under the ROC curve (AUC)= 0.784. Combining miR-423-3p with prostate-specific antigen (PSA) enhanced the prediction of CRPC (AUC= 0.908). A separate research center validation with 30 treatment-naive and 30 CRPC patients also confirmed the differential expression of miR-423-3p (p= 0.016). Finally, plasma exosomal miR-423-3p expression in CRPC patient was compared to 36 non-CRPC patients under androgen depletion therapy, which showed significantly higher expression in CRPC than treated non-CRPC patients (p< 0.0001) with AUC= 0.879 to predict CRPC while no difference between treatment-naive and treated non-CRPC patients. Therefore, we identified a number of plasma exosomal miRNAs associated with CRPC and miR-423-3p may serve as a biomarker for early detection/prediction of castration-resistance.